2010
DOI: 10.1074/jbc.m109.065078
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Caldesmon on the Intermediate Conformational States of Polymerizing Actin

Abstract: The actin-binding protein caldesmon (CaD) reversibly inhibits smooth muscle contraction. In non-muscle cells, a shorter CaD isoform co-exists with microfilaments in the stress fibers at the quiescent state, but the phosphorylated CaD is found at the leading edge of migrating cells where dynamic actin filament remodeling occurs. We have studied the effect of a C-terminal fragment of CaD (H32K) on the kinetics of the in vitro actin polymerization by monitoring the fluorescence of pyrene-labeled actin. Addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 54 publications
(25 reference statements)
2
29
0
Order By: Relevance
“…However, in our experiments, the increased branching occurs on actin filaments aged on a time scale significantly longer than that of phosphate release from actin (30). As has previously been shown, the effect induced by CaD does not involve ATP hydrolysis or phosphate release (9), meaning that virtually all Alexa Fluor 488 actin during the imaging assay was already in the ADP state. Interestingly, a transient post-phosphate release intermediate conformation of actin prior to mature ADP-Factin formation has been detected before (12); such a conformation may be stabilized by CaD.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…However, in our experiments, the increased branching occurs on actin filaments aged on a time scale significantly longer than that of phosphate release from actin (30). As has previously been shown, the effect induced by CaD does not involve ATP hydrolysis or phosphate release (9), meaning that virtually all Alexa Fluor 488 actin during the imaging assay was already in the ADP state. Interestingly, a transient post-phosphate release intermediate conformation of actin prior to mature ADP-Factin formation has been detected before (12); such a conformation may be stabilized by CaD.…”
Section: Resultssupporting
confidence: 61%
“…Notably, CaD has been found to attenuate pyrene fluorescence enhancement of polymerizing actin without altering the rates of elongation and to prolong the early stage rough appearance of actin filaments under negative staining electron microscopy (9, 10). Because these effects were not seen when CaD was added to aged filaments, it was argued that they correspond to a conformational transition of F-actin occurring naturally during polymerization (9). It was further suggested that CaD blocks this transition, thus keeping the actin filament in the nascent state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations